Clinical efficacy and safety of Xuefu Zhuyu decoction in the treatment of diabetic kidney disease: A protocol for systematic review and meta-analysis. Issue 51 (23rd December 2022) - Song, Chaoqun; Zhu, Zhiyue; Liu, Miao; Yang, Wenbo; Bai, Xiaotian; Nan, Zheng
Abstract : Background: Diabetic kidney disease (DKD) is one of the common complications of diabetes, the most crucial cause of end-stage renal disease, and a significant cause of death in diabetes patients. In recent years, Xuefu Zhuyu decoction has also been widely used in treating diabetic nephropathy. However, there need to be more systematic reviews that comprehensively describe the effectiveness and safety of Xuefu Zhuyu decoction in treating DKD. Therefore, we will conduct a systematic review and meta-analysis to evaluate the indicators of Xuefu Zhuyu decoction in the treatment of DKD to provide evidence-based support. Methods: Eligible published randomized controlled trials from January 2005 to October 2022 will be obtained by searching PubMed, Cochrane Library, EMBASE, Web of Science, CNKI, Wanfang, and VIP in Chinese and English. The Cochrane Collaboration Risk of bias tool will be used for methodological quality assessment and risk of bias. The meta-analysis will be performed using Cochrane RevMan 5.4 software. Results: This study will compare the following indicators: the primary outcomes: urinary albumin excretion rate and urea nitrogen. Secondary outcomes: blood creatinine; 24 hours urine protein quantification; glycosylated hemoglobin; fasting blood glucose; 2-hour postprandial blood glucose; total cholesterol; triglycerides; total effective rate; incidence of adverse events. Conclusion: The results of this systematic review will provide an objective, evidence-based basis for judging the efficacy and safety of Xuefu Zhuyu decoction in treating DKD.